CONNECTION OF DEPRESSION, ANXIETY AND IMPULSIVITY WITH THE WAY OF USING MODERN MOBILE PHONES AMONG STUDENTS - Sojević, Milica R; Latas, Milan (Medicinski podmladak, 2018)
Introduction: There is growing evidence that confirms the addictive nature of using a smartphone. Also there is evidence that show the correlation between different psychopathological manifestations and tendencies with the addictive usege of smartphones. The Aim: Within this research we are investigating effects of anxiety, depression and impulsivity in relation to addictive usage of smartphones. This research has three goals: 1) Researching the level of correlation between these personality characteristics( anxiety, depression and impulsivity) and addictive usage of smartphones; 2) Detecting the ways in which anxiety, depression, and impulsivity predict the addictive usege of smartphones. 3) Researching the total effect of these personality characteristics in relation to addictive usage of smartphones. Material and methods : Sample is composed of 482 students from University of Belgrade, 55.4% female. The research type is correlating and non-experimental. The data was collected by questionnaire method. For the anxiety STAI-Y questionnaire was used, the depression - DL, impulsivity - BIS11 and for the addictive usage of smartphones-SABAS. Results: 1) All three personality characteristics are correlating on a statistically significant level with the addictive usage of smartphones, correlation ranging - 0.30-0.32; 2) Depression and impulsivity appeared as significant and indpendent predictors of addictive usage of smartphones, while the anxiety showed the redundant effect on prediction. Correlation between the anxiety and addictive usege is completely explained by the connection of two other predictors with criteria. 3) The research showed that the subjects who simultaneously have two or more enhanced characteristics are more inclined to addicteve usage of smartphone. Conclusion: The research results implicate that the depression and impulsivity represent significant predisposing factors for addictive usage of smartphones. More research is needed within the given subject with the goal of determining the causes and ways the given personality characteristics correlate. Keywords: anxiety; depression; impulsivity; smartphones;